Isolation and transcript analysis of two-component histidine kinase gene Le.nik1 in Shiitake mushroom, Lentinula edodes - Szeto, C.Y.Y.; Wong, Q.W.L.; Leung, G.S.; Kwan, H.S.
Le.nik1, a two-component histidine kinase gene of Lentinula edodes, the Shiitake mushroom, was identified. The relationship between this two-component signal transduction system and mushroom development was studied. We used a modified RNA arbitrarily-primed PCR (RAP-PCR)method to isolate Le.nik1 as a differentially expressed gene during L. edodes development. We determined the 6.29 kb full-length cDNA sequence of Le.nik1. It had high sequence homology to Neurospora crassa nik1, which encoded a histidine kinase essential for development and osmotic response. In L. edodes, the expression level of Le.nik1 was highest during primordium formation and fruiting body maturation. The transcripts were localized predominantly in the developing hymenophores, or mushroom gills, which may indicate the role of a two-component signal transduction systemin cell differentiation during mushroom development. Mannitol stress influenced transcript expression of Le.nik1, suggesting that it may be involved in osmo-sensing and regulation. To our knowledge, this is the first report on the two-component system in mushrooms and the first analysis on the distribution of Le.nik1 transcript in the course of fruiting body formation and in parts of fruiting bodies.
Keywords: IN SITU RNA-RNA HYBRIDIZATION; MANNITOL STRESS; OSMOREGULATION; TRANSCRIPT EXPRESSION AND LOCALIZATION; TWO-COMPONENT SYSTEM